Her is how to do it hope it helps you!
Answer:
x^(1/3)
Step-by-step explanation:
let's start with x^2 / x^(2/3), then we'll move on the the 4th root
when dividing exponents with the same base, we subtract the exponents:
x^2 / x^(2/3) = x^(2 - 2/3) = x^(4/3)
the fourth root of x^4/3 can become x^(4/3 * 1/4)
(i used the formula x^(m/n) = nth root of x^m)
x^(4/3 * 1/4) = x^1/3
hope this helps! <3
The answer to your question is ( points ).
Answer:
Step-by-step explanation:
<em>Step 1: Determine quantity per liquid</em>
liquid 1=7/8 cup
liquid 2=9/10 cup
<em>Step 2: Derive expression to calculate total amount of mixture</em>
The expression below can be derived;
T=a+b
where;
T=total amount of mixture
a=total amount of liquid 1
b=total amount of liquid 2
In our case;
a=7/8 cup
b=9/10 cup
replacing;
T=(7/8)+(9/10)=1 31/40 cups
The total amount of mixture=1 31/40 cups